2016
DOI: 10.3390/agriculture6040051
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Accumulation of Heavy Metals in an Industrial Wheat Crop from Uranium Mine Soil and the Potential Use of the Herbage

Abstract: Abstract:Testing the quality of heavy-metal (HM) excluder plants from non-remediable metalliferous soils could help to meet the growing demands for food, forage, and industrial crops. Field cultures of the winter wheat cv. JB Asano were therefore established on re-cultivated uranium mine soil (A) and the adjacent non-contaminated soil (C). Twenty elements were determined by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) from soils and plant sections of post-winter seedlings, anthesis-state, and mature p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 94 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…However, it should be noted that feeding these vegetables, including their peel, to livestock can introduce U into the human food chain. The negative impact of U contamination is evident through reduced yields of vegetables (up to 87%) reported by Neves and Abreu [77] and Neves et al [72,77], and reduced yields of cereals (up to 47.7%) reported by Gramms and Voigt [78]. S2).…”
Section: Occurrence Of Uranium In Soil-plant Systemmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it should be noted that feeding these vegetables, including their peel, to livestock can introduce U into the human food chain. The negative impact of U contamination is evident through reduced yields of vegetables (up to 87%) reported by Neves and Abreu [77] and Neves et al [72,77], and reduced yields of cereals (up to 47.7%) reported by Gramms and Voigt [78]. S2).…”
Section: Occurrence Of Uranium In Soil-plant Systemmentioning
confidence: 94%
“…In leafy and cereal crops, U accumulation was most prominent in (decreasing order) the roots/straws, leaves, and edible parts (grains/fruit) [82,83]. Conversely, in non-leafy vegetables, the peels and tubers exhibited a higher accumulation of U (up to 90%) due to their elevated surface area and starch content [78,[84][85][86]. While, Shanthi et al [87] s demonstrated that edible tubers tend to contain higher levels of radionuclides compared to vegetables.…”
Section: Occurrence Of Uranium In Soil-plant Systemmentioning
confidence: 99%
“…Similar deficits in the contribution of rhizomes of terrestrial and maritime grasses to the plants' N and P budget seem to be common [46,47]. Whereas in wheat crops the grains may account for up to 45% of the total biomass furnished by an unbroken allocation of soil constituents until maturity (e.g., [59]), the microscopic seeds formed by 20,000 per goldenrod plant with a 1000-seed fresh weight of 45-50 mg [60] are no notable sink of minerals and organics. The shoots' 23% drop in DW from blooming to maturity must therefore be attributed to a drain in water-soluble organics (95.7%) and the group of CaKMgNP (4.3%, w/w) no longer in need but virtually not to the discard of solid biomass ( Table 2).…”
Section: Turnover Of Organics and Minerals In The Goldenrod Colonymentioning
confidence: 96%
“…According to the Ministry of Agriculture and Agro-based Industry, rice production declined 3.2 % in 2018 from the previous year. Although there are many factors that may affect rice production, reports have shown that the presence of heavy metals in the soil can reduce rice yields and may have negative effects to human health (Gramss & Voigt, 2016).…”
Section: Problem Statementmentioning
confidence: 99%